Implementasi Bussiness to Customer (B2C) untuk Optimalisasi Promosi Produk Olahan Makanan dan Minuman Buah Parijoto Meethos Desa Kuwukan, Dawe Kudusimplementasi Bussiness To Customer (B2c) Untuk Optimalisasi Promosi Produk Olahan Makanan dan Minuman Buah Parijoto Meethos Desa Kuwukan, Dawe Kudus - Diana Laily Fithri; Rhoedy Setiawan; Fajar Nugraha (ABDIPRAJA (Jurnal Pengabdian kepada Masyarakat), 2022)
Kuwukan Village, which is one of the villages in the Dawe sub-district, Kudus district. In the mountainous area of Muria, which has an altitude between 800-1200 masl, including the highlands, it is very suitable for parijoto cultivation, so many people in this area cultivate Parijoto plants. The marketing process for the Parijoto Meethos fruit food and beverage products is still done conventionally, so that the marketing reach is still limited around the city of Kudus, or through privately owned business shops. Although there were some requests from out of town but the numbers were still small due to lack of promotion. Limited resources are the main reason for producers of parijoto food and fruit to be able to use information technology in the promotion and marketing process. The purpose of implementing this community service activity is to help increase the income and welfare of parijoto food and fruit producers in Kudus Regency by utilizing information technology through the implementation of an e-commerce website with the Business to Customer (B2C) concept. The method used in this service program is to implement and train the use of websites with the concept of Business to Customer (B2C) to overcome the problems of limited marketing experienced by producers of parijoto food and fruit in using information technology. Keywords: parijoto, promotion, marketing, business to customer (B2C).